1987
DOI: 10.1111/j.1365-2141.1987.tb06926.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet reactions after interaction with cultured Plasmodium falciparum infected erythrocytes

Abstract: An in vitro model for studying the interaction between normal human platelets and Plasmodium falciparum infected erythrocytes in culture is described. After the interaction, changes in platelet function such as enhanced aggregation response to exogenous ADP and increased secretion of dense granule contents were reproduced. Some of these responses represented manifestations of platelet hypersensitivity described earlier in acute malaria infections in man and mice. Preliminary investigations of the mechanisms in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

1989
1989
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 11 publications
1
12
1
Order By: Relevance
“…Whether a systemic activation of circulating platelets occur in malaria is still unclear. While a study has reported altered platelet responses after exposure to P. falciparum infected erythrocytes (P-IE) in vitro (22), direct assessment of platelet activation through flow cytometry has rendered negative results (10, 23). However, evidence of some grade of platelet activation in vivo , through measurement of circulating factors, have been shown by other groups (5, 24).…”
Section: Discussionmentioning
confidence: 99%
“…Whether a systemic activation of circulating platelets occur in malaria is still unclear. While a study has reported altered platelet responses after exposure to P. falciparum infected erythrocytes (P-IE) in vitro (22), direct assessment of platelet activation through flow cytometry has rendered negative results (10, 23). However, evidence of some grade of platelet activation in vivo , through measurement of circulating factors, have been shown by other groups (5, 24).…”
Section: Discussionmentioning
confidence: 99%
“…26 Additionally, humans infected with the parasite Trypanosoma cruzi and other infectious agents suffer from severe thrombocytopenia due to mobilization of sialic acid from the circulating platelets. [27][28][29] In preliminary experiments, we have found that removal of the external domain of GP1b␣ carrying complex type N-linked glycans from the platelet surface by O-sialoglycoprotein endopeptidase decreased the clearance rate of transfused platelets stored at 4°C for 24 hours (data not shown). This may suggest that domains or glycans on the external part of GP1b␣ are important for the clearance of long-term 4°C-stored platelets.…”
Section: Discussionmentioning
confidence: 99%
“…Maximum induction ofADP-induced platelet aggregation was found in P. falciparum infection as compared to P. vivax malaria which reflects the vulnerability of these patients to develop platelet aggregation induced complications and endothelial injury evidenced by establishment of significant negative correlation between ADP induced platelet aggregation and hemoglobin concentration (r = -0.637) ( Figure 2). Inyang et al (19) allowed the interaction of normal platelets with R falciparum and found significant increase in aggregation response of the platelets to external stimuli such as ADP, which exhibits the platelet dysfunction. Another reason behind the increased platelet aggregation in malaria patients might be upsurged lipid peroxidation.…”
Section: I) Alterations In Hematological Parametersmentioning
confidence: 99%